What Happens After the Intervention? Results From Teacher Professional Development in Employing Mathematical Reasoning Tasks and a Supporting Rubric - Smit, Robbert; Hess, Kurt; Bachmann, Patricia; Blum, Verena; Birri, Thomas (Frontiers in Education, 2019)
The lasting effects of teacher professional developments (PDs) are seldom surveyed. We investigated whether 44 teachers and their 5th- and 6th-grade primary classes continued working with tasks for mathematical reasoning and employing a rubric after the PD. Questionnaires for students and teachers were administered before the intervention, at the end of the intervention, and five months later. The results of the quantitative longitudinal analyses with supplemental qualitative interpretations indicate that the mathematical features of our PD show more sustainable effects than the rubric. Explorative findings suggest that this outcome may be related to the teachers’ pedagogical content knowledge.